2010
DOI: 10.1007/s12517-010-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of near-surface geotechnical parameters using seismic measurements at the proposed KACST expansion site, Riyadh, KSA

Abstract: Eight shallow seismic refraction profiles were conducted at the proposed KACST expansion site, northwest of Riyadh, to estimate the near-surface geotechnical parameters for construction purposes. Both compressional (P) and shear (S) waves were acquired, processed, and interpreted using "time-term" technique which is a combination of linear least squares and delay time analysis to invert the first arrivals for a velocity section. The most important geotechnical near-surface parameters such as stress ratio, Pois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…As a combined result of the above, based on the results of this work and other previous geotechnical works (Almalki et al, 2011;Khalil and Hanafy, 2016;Khorshid, 2016;Abudeif et al, 2017;Adewoyin et al, 2017;Shebl et al, 2019;Momoh et al, 2020;Ghanem et al, 2021;Basheer and Salama, 2022), It can be found that there is a direct relation between the concentration index, material index, and N value for being low for low competent material and increase as it becomes more competent. Inversely, the stress ratio, Poisson's ratio, and density gradient values are high for low competent material and decrease as it becomes more competent.…”
Section: Allowable Bearing Capacity (Qa)supporting
confidence: 77%
See 1 more Smart Citation
“…As a combined result of the above, based on the results of this work and other previous geotechnical works (Almalki et al, 2011;Khalil and Hanafy, 2016;Khorshid, 2016;Abudeif et al, 2017;Adewoyin et al, 2017;Shebl et al, 2019;Momoh et al, 2020;Ghanem et al, 2021;Basheer and Salama, 2022), It can be found that there is a direct relation between the concentration index, material index, and N value for being low for low competent material and increase as it becomes more competent. Inversely, the stress ratio, Poisson's ratio, and density gradient values are high for low competent material and decrease as it becomes more competent.…”
Section: Allowable Bearing Capacity (Qa)supporting
confidence: 77%
“…Shallow seismic refraction is an efficient method for quickly identifying the geotechnical parameters in engineering and construction projects (Almalki et al, 2011;Khalil and Hanafy, 2016;Khorshid, 2016;Abudeif et al, 2017;Adewoyin et al, 2017;Shebl et al, 2019;Momoh et al, 2020;Ghanem et al, 2021). The ground's soil is the only building material with more changeable engineering and physical characteristics that vary both laterally and vertically (Bowles, 1982).…”
Section: Geotechnical Parametersmentioning
confidence: 99%
“…One of the Frontiers in Earth Science frontiersin.org 10 seismic survey techniques for determining the elastic condition (stiffness) of the ground for geotechnical engineering purposes is the multichannel analysis of surface waves (MASW) approach. For a variety of geotechnical investigations, using surface wave propagation to get shear wave velocities (Vs) profiles have proven to be a promising technique (Soupois et al, 2007;Almalki et al, 2011;Busato et al, 2016;Liu et al, 2016;Shen et al, 2016;Aldahri et al, 2017;Rahimi et al, 2018;Cardarelli et al, 2018;Hu and Liu, 2019;Mogren et al, 2020;Sena Lozoya et al, 2020;Alamri et al, 2020;Alzahrani et al, 2021a;Alzahrani et al, 2021b;Alzahrani M. et al, 2022;Abd El-Raouf et al, 2021 and;Abd El-Raouf et al 2022). These investigations mainly include building-ground studies, site assessment, determination of the physical properties of rocks and delineating subsurface cavities and weak zones, etc.…”
Section: Multi-channel Analysis Of Surface Waves (Masw)mentioning
confidence: 99%
“…Our area under investigation lies on the shoreline, so it is essential to study the intrusion of water in the layers and any abnormal changes in the homogeneous layers that reflect clay lenses to avoid them (Alshehri et al 2021;Satheeskumar et al 2021;Basheer and Salama 2022). In SSR method, the velocity provides a mechanism for measuring the strength and evaluating the quality of rock materials, since it depends on the density and elasticity of the material through, which the energy is passed (Almalki et al 2011;Comina et al 2021;Ray et al 2021). Because beach sand makes up the surface of the study area, it is crucial to understand the geotechnical properties of the various strata and how they affect the height of structures that are planned to be built (Sakr et al 2021;Basheer and Salama 2022).…”
Section: Introductionmentioning
confidence: 99%